Obstetrical Complications and Outcomes in Adolescent Primigravidas Comparative with Older Primigravidas in Tishreen University Hospital - نعيسة ثورة; النقري محمد; الأحمد سحر (Latakia University Journal -Medical Sciences Series, 2021)
- Objective: This research aims to study the incidence of obstetric complications (parental and neonatal) among primigravid adolescents at Tishreen University Hospital. - Methods: A Cross-Sectional Study of a case-control type, conducted at the Department of Obstetrics and Gynecology Diseases at Tishreen University Hospital between 1/1/2019 - 1/1/2020, and included 130 primigravid adolescents (14-19 years of age) as a cases group and 130 older primigravid (aged 20 years). 34 years old) as a control group. - Results: Among the primigravid adolescents, the gestational age and education level was lower than the older primates, and the difference was statistically significant. Primigravid adolescents were more likely to have complications during pregnancy such as anemia (OR = 1.5, 95% CI 0.9-2.5), gestational diabetes (OR = 1.3, 95% CI 0.9-2.5), gestational hypertension (OR = 1.2, 95% CI 0.6-2.4), pre-eclampsia (OR = 1.5, 95% CI 0.6-3.4) and eclampsia (OR = 1.7, 95% CI 0.4-7.2), but the difference was not statistically significant. The incidence of obstetric complications was higher in the primigravid adolescents, such as antepartum hemorrhage (OR =1.7, 95% CI 0.4-7.2), preterm labor (OR = 1.9, 95% CI 1-3.4), prolonged second labor stage (OR =1.4, 95% CI 0.5-4), perineal tear (OR = 2.1, 95% CI 0.8-5.4), postpartum hemorrhage (OR = 1.9, 95% CI 0.8-5.1), and blood transfusion during childbirth (OR = 1.5 , 95% CI 0.7-3.4). We also found an increase in fetal complications, such as intra-uterine growth retardation (OR = 1.8, 95% CI 0.5-6.3), low birth weight (OR = 1.5, 95% CI 0.7-3), and the need for admission to the incubator (OR = 2.1, 95% CI). 1.1-4.4), and postpartum death (OR = 1.7, 95% CI 0.4-7.2). - Conclusion: Primigravid adolescents are more likely to have complications during pregnancy, childbirth, and fetal complications. Health education and raising the level of community awareness can lead to a reduction in the rate of adolescent pregnancy and the associated complications for the mother and fetus.